Factors Influencing Stress and Coping Strategies among the College Teachers of Kerala State - K.P. Sindhu
The study on factors influencing stress and coping strategies was conducted on a random sample of 200 (100 each of male and female) degree college teachers of Kerala State. Questionnaire for Demographic characteristic and Coping Strategies were used along with Employment Organization Sources of Stressors scale (Telaprolu and George, 2005). Frequency, percentage, t-test, correlation and step wise regression were used for analysis. The factors that caused stress always were mainly due to the interference of the employment organizational responsibilities with their family organizational role, lack of their involvement in decision making that reduced their responsibilities and the participatory model in their organizational set up which enhanced their responsibilities to the point of exhaustion. Majority of the teachers revealed that stress was basically due to their laziness and also they were happy with fewer responsibilities.